(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Ivakh S. The features of parents’ pedagogisation of preschool children. The article emphasizes the importance of the close relationship of the family and kindergarten to create one for each childsentrystic educational environment. It also singles out the basic principles of their interaction and substantiates effective forms and methods of their collaboration.